Direct Observation of Spin States Involved in Organic Electroluminescence Based on Thermally Activated Delayed Fluorescence. Issue 3 (20th December 2016) - Väth, Stefan; Tvingstedt, Kristofer; Auth, Michael; Sperlich, Andreas; Dabuliene, Asta; Grazulevicius, Juozas V.; Stakhira, Pavlo; Cherpak, Vladyslav; Dyakonov, Vladimir
Abstract : The first application of electroluminescence detected electron spin resonance technique on electroluminescent thermally activated delayed fluorescence (TADF) devices is shown. It indubitably proves the involvement of spins in the emergence of TADF electroluminescence and reveals the temperature dependency of such spin‐dependent processes on bilayer devices that consist of two different material systems.